Exploring advances in interdisciplinary data mining and analytics new trends - Taniar, David; Iwan, Lukman Hakim, 1976-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book is an updated look at the state of technology in the field of data mining and analytics offering the latest technological, analytical, ethical, and commercial perspectives on topics in data mining"--Provided by publisher.
12. Constrained cube lattices for multidimensional database mining / Alain Casali ... [et al.] -- 13. ASCCN: arbitrary shaped clustering method with compatible nucleoids / Renxia Wan, Lixin Wang and Xiaoke Su -- 14. A new similarity metric for sequential data / Pradeep Kumar, Bapi S. Raju and P. Radha Krishna -- 15. When spatial analysis meets OLAP: multidimensional model and operators / Sandro Bimonte ... [et al.] -- 16. Combining kNN imputation and bootstrap calibrated: empirical likelihood for incomplete data analysis / Yongsong Qin, Shichao Zhang and Chengqi Zhang.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed November 19, 2011).
Keywords: Data mining; Web usage mining; Association rules; Business intelligence; Classification; Data aggregation; Decision making; Market basket analysis; Modeling; Patterns and pattern mining; Regression; Results validation; Electronic books